Punish One, Teach A Hundred: The Sobering Effect of Punishment on the Unpunished - Francesco D'Acunto; Michael Weber; Jin Xie (Center for Economic Studies and ifo Institute (CESifo), 2019)
Direct experience of a peer's punishment might make non-punished peers reassess the probability and consequences of facing punishment and hence induce a change in their behavior. We test this mechanism in a setting, China, in which we observe the reactions to the same peer's punishment by listed firms with different incentives to react - state-owned enterprises (SOEs) and non-SOEs. After observing peers punished for wrongdoing in loan guarantees to related parties, SOEs - which are less disciplined by traditional governance mechanisms than non-SOEs - cut their loan guarantees. SOEs whose CEOs have stronger career concerns react more than other SOEs to the same punishment events, a result that systematic differences between SOEs and non-SOEs cannot drive. SOEs react more to events with higher press coverage even if information about all events is publicly available. After peers' punishments, SOEs also increase their board independence, reduce inefficient investment, increase total factor productivity, and experience positive cumulative abnormal returns. The bank debt and investment of related parties that benefited from tunneling drop after listed peers' punishments. Strategic punishments could be a cost-effective governance mechanism when other forms of governance are ineffective.
Keywords: D91; D72; G32; G41; K42; 330; corporate governance; cultural finance; reputational sanctions; related party transactions; minority shareholders; emerging markets; corporate fraud; government ownership